Spent Craft Brewer's Yeast Reduces Production of Methane and Ammonia by Bovine Rumen Microbes - Bryant, Robert W.; Burns, E. E. Rhys; Feidler-Cree, Christopher; Carlton, Denia; Flythe, Michael D.; Martin, Langdon J. (Frontiers in Animal Science, 2021)
Methane and ammonia are byproducts of rumen fermentation that do not promote animal growth, and methane is a key contributor to anthropogenic climate disruption. Cows eructate every few breaths and typically emit 250–500 L of methane gas daily. Significant research is focused on finding diets and additives that lower the production of methane and ammonia. Emerging research has shown that humulones and lupulones, molecules that are found in the cones of hops (Humulus lupulus), have potential in this regard. These molecules, which are also key flavor components in beer, are biologically active: they are known inhibitors of Gram-positive bacteria. Ruminants' sophisticated digestive systems host billions of microorganisms, and these systems' outputs will likely be affected in the presence of brewer’s yeast (Saccharomyces cerevisiae). So-called spent yeast is produced during the beer-brewing process and contains humulones and lupulones in concentrations that vary by beer style, but is generally discarded as waste. Our research suggests that adding spent craft brewer’s yeast to rumen microbes in vitro suppresses production of methane and ammonia. This project examines the correlation between the quantities of hop acids in spent yeast and the production of methane and ammonia by bovine rumen microbes in vitro. We determined, by HPLC, the hop acid concentrations in spent yeast obtained from six beer styles produced at a local brewery. We performed anaerobic incubation studies on bovine rumen microbes, comparing the effects of these materials to a baker’s yeast control and to the industry-standard antibiotic monensin. Results include promising decreases in both methane (measured by GC–FID) and ammonia (measured by colorimetric assay) in the presence of craft brewer’s yeast, and a strong correlation between the quantities of hop acids in the spent yeast and the reduction of methane and ammonia. Notably, two of the yeast samples inhibited methane production to a greater degree than the industry-standard antibiotic monensin. Our results suggest that spent brewer’s yeast has potential to improve ruminant growth while reducing anthropogenic methane emission.